2001
DOI: 10.1021/tx010029w
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Rates of Isothiocyanate Conjugates Determine Their Activity as Inhibitors of Cytochrome P450 Enzymes

Abstract: Thiol conjugates of isothiocyanates (thiol-ITCs) are metabolites of ITCs formed in the mercapturic acid pathway in mammals. They are effective chemopreventive agents in mouse lung tumor bioassays and in other models. Thiol-ITCs are inhibitors of P450s, but it has not been determined if P450 inhibition is due to conjugates themselves or to parent ITCs released by deconjugation reactions. In studies of mechanism of chemopreventive action of thiol-ITCs, rates of deconjugation of Cys, GSH, and N-acetyl-L-cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 32 publications
(57 reference statements)
3
98
0
2
Order By: Relevance
“…[10][11][12]. NAC-ITCs are unstable and dissociate to release isothiocyanates (4,13), and storage of urine containing NAC-ITCs in the bladder likely further enhances the exposure of bladder cells to these compounds. As a result, the bladder epithelium that gives rise to the majority of bladder cancers (90-95% in the United States; ref.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12]. NAC-ITCs are unstable and dissociate to release isothiocyanates (4,13), and storage of urine containing NAC-ITCs in the bladder likely further enhances the exposure of bladder cells to these compounds. As a result, the bladder epithelium that gives rise to the majority of bladder cancers (90-95% in the United States; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Isothiocyanate-GSH conjugates may have been formed, which are typically metabolized to yield cysteinylglycine-, cysteine-and N-acetylcysteine conjugates that are eliminated easily and concentrated in the urine. Research has shown that N-acetylcysteine conjugates and the intermediate metabolites of ITCs, which are collectively known as dithiocarbamates (DTCs) are unstable and easily dissociate to their parent ITCs (Conaway et al 2001). This explains the sudden increase in the concentration of 1, 3-benzodithiole-2-thione formed on day 3 (Fig.…”
Section: Use Of Biodegradation Techniques For Bitc Degradationmentioning
confidence: 99%
“…PHOX of NADPH oxidase (Nox2), 92) adenine nucleotide translocase, 93) CYP isozyme, 106) histone deacetylase, 107) a transient receptor potential (TRP) family of ion channels (TRPA1), 108) and so on. Among ITCs, phenyl ITC (PITC) is a unique inactive ITC but has electrophilic reactivity to modify protein function in vitro.…”
Section: Chemistry Metabolism and Molecular Targets Of Isothiocyanatesmentioning
confidence: 99%
“…The decomposition of thiol conjugates of ITCs is also pH dependent. 106) A mechanism for the influence of hydroxyl ions on the decomposition of thiol conjugates of ITCs has been proposed: A hydroxyl ion deprotonates the conjugate nitrogen, leading to elimination of the thiol leaving group and regeneration of the ITC. The physiological implication of the influence of pH on thiol-ITC decomposition is that orally administered thiol-ITCs remain intact when absorbed through the stomach mucosa, but probably dissociate to ITCs to a much greater extent in the intestinal tract.…”
Section: Chemistry Metabolism and Molecular Targets Of Isothiocyanatesmentioning
confidence: 99%
See 1 more Smart Citation